Meningkatkan Keaktifan Siswa melalui Pembelajaran Kooperatif STAD pada Mata Pelajaran PPKn - Nibras Shohwatul Islam; Mahfiroh Fitria Maulani; Nenden Rosita; Prima Melati; Tetep Tetep; Anita Murdayanti (PTK: Jurnal Tindakan Kelas, 2025)
The activeness of students in PPKn learning in class IX C SMPN 5 Tarogong Kidul is still low, shown by the lack of participation in discussions, asking questions, and dominance of lecture methods. This research aims to increase student activity through a cooperative learning model of the Student Teams Achievement Division (STAD) type. The research uses the Classroom Action Research (PTK) approach with the DDAER model, carried out in two cycles. Data collection techniques include observation, interviews, and documentation. The activity of students increased from 33.3% in the pre-cycle to 54.2% in the first cycle, and 87.5% in the second cycle. Improvements occurred in all indicators, especially in questioning, discussion, and group cooperation. The implementation of STAD by teachers also increased from 83.3% to 100%. The application of the STAD model is consistently effective in increasing students' activeness in PPKn learning, both individually and in groups.